Clonality, spatial structure, and pathogenic variation in Fusarium fujikuroi from rain-fed rice in southern Laos. - Barbara Scherm; Virgilio Balmas; Alessandro Infantino; Maria Aragona; Maria Teresa Valente; Francesca Desiderio; Angela Marcello; Sengphet Phanthavong; Lester W Burgess; Domenico Rau (PLoS ONE)
Bakanae disease, caused by the fungal phytopathogen Fusarium fujikuroi, can be detected in most rice (Oryza sativa L.) growing areas worldwide. In this study, we investigated the population structure of this fungus in southern Lao PDR, a country located near the geographic origin of rice domestication. Microsatellites (SSRs) and mating type (MAT) analyses, pathogenicity and fungicide sensitivity tests were integrated in the study. The first key finding is that the population genetic structure of F. fujikuroi in Lao PDR is consistent with high clonal reproduction. Indeed, (i) "true" clones were identified; (ii) within populations, MAT types were frequently skewed from 1:1 ratio, (iii) linkage disequilibrium (among SSRs as also among SSRs and MAT) was present, and (iv) gene-flow between opposite MAT types within the same population is restricted. The presence of genetic divergence among areas and populations and the occurrence of positive spatial autocorrelation of genetic variation, indicate that migration is restricted, and that genetic drift plays an important role in the evolution of this fungus. Two main well-defined groups of isolates were detected (FST = 0.213) that display a non-random spatial distribution. They differ in the ability to induce seedlings death but not seedlings elongation (the typical Bakanae symptom) suggesting that the pathogen's ability to induce the two symptoms is under different genetic control. Finally, we compared two agroecosystems with contrasting characteristics: low-input and traditional (Lao PDR) vs high-input and modern (Italy). We found differences in the level of population structuring and of spatial autocorrelation. This suggests that the evolutionary potential of the fungus not only depends on its intrinsic characteristics, but is strongly influenced by other external factors, most likely by the dynamics of infested seed exchange. Thus, quarantine and chemical treatments are a way to reduce population connectivity and hence the evolutionary potential of this pathogen.